Use of Tubular Retractors for Minimally Invasive Resection of Deep-Seated Cavernomas. Issue 6 (13th July 2019) - Eichberg, Daniel G; Di, Long; Shah, Ashish H; Ivan, Michael E; Komotar, Ricardo J; Starke, Robert M
Abstract: BACKGROUND: Cavernomas located in subcortical or eloquent locations are difficult lesions to access safely. Tubular retractors, which distribute retraction pressure radially, have been increasingly employed successfully. These retractors may be beneficial in subcortical cavernoma resection. OBJECTIVE: To review a single institution's case series to determine the safety profile and efficacy of transcortical-transtubular cavernoma resections and to describe our transtubular operative technique. METHODS: We reviewed a single institution's transcortical-transtubular cavernoma resections using either BrainPath (NICO, Indianapolis, Indiana) or ViewSite Brain Access System (Vycor Medical, Boca Raton, Florida) tubular retractors performed from 2013 to 2018 (n = 20). RESULTS: Gross total resection was achieved in all patients. When a developmental venous anomaly (DVA) was present, avoidance of DVA resection was achieved in all cases (n = 4). All patients had a supratentorial cavernoma with mean depth below cortical surface of 44.1 mm. Average postoperative clinical follow-up was 20.4 wk. Early neurologic deficit rate was 10% (n = 2); permanent neurologic deficit rate was 0%. One patient (5%) experienced early postoperative seizures (< 1 wk postop). No patients experienced late seizures (> 1 wk follow-up). Engel class 1 seizure control at final clinical follow-up was achieved in 87.5% of patients presenting with preoperative epilepsy. CONCLUSION: Tubular retractors provide a low-profile, minimally invasive operative corridor for resection of subcortical cavernomas. There were no permanent neurologic complications in our series of 20 cases, and long-term seizure control was achieved in all patients. Thus, tubular retractors appear to be a safe and efficacious tool for resection of subcortical cavernomas.